Effects of honey, glutamine and their combination on canine small bowel epithelial cell proliferation following massive resection (2012)
The effects of honey, glutamine and honey/glutamine combination on the healing and adaptive process of the bowel following massive small bowel resection were studied in some Nigerian non-descript breeds of dogs. 24 dogs (3-4months old) of mixed sexes with mean body weight of 4.42±0.70 kg were studied. They were randomized into four treatment groups following 70% small bowel resection. Group A dogs were placed on glutamine treatment, Group B on oral glutamine/honey and group C on honey and group D normal saline (control). Their body weights were evaluated for 15 days and the pre- and post-treatment gut biopsy samples were obtained and processed for morphometric evaluation. All groups exhibited signs of small bowel adaptation (Glutamine/honey>glutamine > honey > control) at the end of the experiment (4 weeks). Glutamine/honey combination, glutamine and honey had gradual increase in body weight from days 3-15 of weight evaluation. The control group, however, had a remarkable drop in body weight compared with other groups. Oral glutamine/honey combination showed the best overall effect based on body weight gain, intestinal mucosal growth and adaptation, evidenced by increased in residual bowel Villi height (27.71μm), Villi weight (14.51μm), Crypt depth (11.25μm), and Villi density (3.40μm). Glutamine showed a better result than honey with a significant increase in villi height (38.08μm), width (8.48μm) and crypt depth (40μm). Histologically, an improved villi branching was observed with glutamine/honey combination. Our results showed that honey/glutamine combination had comparative therapeutic advantage over glutamine or honey and may be a preferred treatment for short bowel syndrome patients